Silicate fertilization potentiates the nodule formation and symbiotic nitrogen fixation in soybean - Steiner, Fabio; Zuffo, Alan Mario; Bush, Aecio; Silva Santos, Diego Muniz da [UNESP] (Univ Federal Goias, 2018)
The application of silicon (Si) to the soil can increase the grain yield of the soybean crop by improving the nitrogen biological fixation, due to its beneficial effect on the Bradyrhizobium-soybean symbiosis. This study aimed to investigate the effect of fertilization with calcium and magnesium silicate on plant growth, root nodulation and nitrogen (N) uptake, in two soybean cultivars [BRS 1074 IPRO (transgenic) and BRS-MG 800A (conventional)], under greenhouse conditions. The application of silicate significantly increased the number of root nodules only for the BRS-MG 800A, while the positive effects of the silicate addition on nodule size, chlorophyll level and leaf N concentration were observed in both cultivars. The soybean cultivars show distinct responses to the silicate application, with respect to growth and dry matter yield, being the BRS 1074 IPRO more responsive than the BRS-MG 800A. Therefore, Si may induce the formation of root nodules in soybean plants and lead to significant increases in the nitrogen biological fixation and plant growth. These results highlight that Si is not only involved in the improvement of plant growth, but it can be also considered a crucial element to improve the symbiotic performance of soybean plants. However, the physiological basis of how and where silicate exerts its influence on nodulation and nitrogen biological fixation still remains unknown.